Ageing is associated with disrupted reinforcement learning whilst learning to help others is preserved - Jo Cutler (Nature Portfolio, 2021)
Evidence suggests older adults engage in more prosocial behaviours compared to younger people. Here the authors investigate prosocial reinforcement learning rates in young and older adults.